Field tests in wheelchair Mini-basketball - Delussu, A. S.; Brunelli, S.; Averna, T.; Polidori, L.; Di Giusto, C.; Damas Ntendarere, D.; Traballesi, M. (Medicina dello Sport, 2011)
Aim. The aim of this paper was to select field tests to assess specific wheelchair mini-basketball skills (SWMBS), to determine their repeatability and to evaluate changes in SWMBS after six months of training using the same tests.